Determinan Nilai Perusahaan pada Perusahaan Konsumen Primer - Rida Anisa Permata; Ediwarman Ediwarman (Journal of Management and Business Review, 2023)
This study aims to determine whether there is an influence between financial performance (ROA) and firm size with the natural logarithm (LN) of total assets and capital structure (DER) on firm value (PBV) in primary consumer goods companies. The population of 92 companies listed on the IDX in the primary consumer goods industry sector is 2016-2020. Furthermore, in this study, there were 58 companies as a sample using the purposive sampling method. This type of research is classified into quantitative research and the application of a significance level of 5%. From the results of hypothesis testing and analysis using the Panel Data Regression Analysis technique, it was found that financial performance with return on assets stated a positive and significant effect on firm value, firm size with LN (total assets) had a negative and significant effect on firm value and capital structure. Furthermore, with debt to equity ratio has a positive and significant effect on firm value.